Two new species of the genus Gnaptorina Reitter from the Hengduan Mountains, China (Coleoptera: Tenebrionidae: Blaptini) - Li, Xiu-Min; Bai, Xing-Long; Ren, Guo-Dong (Zootaxa, 2019)
Two new species of nominal subgenus of Gnaptorina Reitter, 1887 (Coleoptera, Tenebrionidae: Blaptini), G. (G.) acutangula sp. nov., G. (G.) crassitibia sp. nov., are described from the Hengduan Mountains, Western Sichuan province of China. A key to the known species of the subgenus Gnaptorina is provided.